PENDERITAAN MANUSIA DAN KEADILAN TUHAN PERSPEKTIF TAFSȊR AL-MISHBĀH - Arif Rahman Hakim; Abd Muid Nawawi; Muhammad Adlan Nawawi (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2023)
This study discusses human suffering and God's justice from the perspective of Tafsȋr al-Mishbāh. This research departs from the pros and cons of human suffering when it is related to God's Justice. This literature review confirms that the source of human suffering is the result of sin, violating God's commandments, the test of life, human free will, and natural conditions as factors that contribute to human suffering including conditions of deprivation, adequacy, life's difficulties and convenience, natural conditions such as disease. , poverty, natural disasters, or physical or mental conditions that result in suffering. In the context of God's justice, circumcision and destiny are interrelated. Although humans may not always understand or feel such justice, the belief that God's justice is reflected in His sunatullah and destiny can provide a framework for understanding human suffering and God's role in overcoming suffering. Human suffering and God's justice emphasize the values of belief in God's justice, patience in life's tests and trials, self-introspection, taking wisdom and learning from suffering, cultivating empathy and trustworthiness